Rocking the hand that rocks the cradle : exploring the potential of group therapy with low-income South African mother-infant dyads - Spedding, Maxine F. (Stellenbosch : Stellenbosch University, 2012)
Assignment (MA)--University of Stellenbosch, 2005.